2010
DOI: 10.3345/kjp.2010.53.10.863
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome in children: Epidemiology, pathophysiology, diagnosis and sequelae

Abstract: The prevalence of pediatric obstructive sleep apnea syndrome (OSAS) is approximately 3% in children. Adenotonsillar hypertrophy is the most common cause of OSAS in children, and obesity, hypotonic neuromuscular diseases, and craniofacial anomalies are other major risk factors. Snoring is the most common presenting complaint in children with OSAS, but the clinical presentation varies according to age. Agitated sleep with frequent postural changes, excessive sweating, or abnormal sleep positions such as hyperext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
1
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 82 publications
(87 reference statements)
4
81
1
13
Order By: Relevance
“…Obesity is a major risk factor for the OSA, with body mass index (BMI), visceral fat and neck circumference being important predictors of its clinical expression. Reduced overall performance in adolescents stems directly from this condition 8,9 .…”
mentioning
confidence: 99%
“…Obesity is a major risk factor for the OSA, with body mass index (BMI), visceral fat and neck circumference being important predictors of its clinical expression. Reduced overall performance in adolescents stems directly from this condition 8,9 .…”
mentioning
confidence: 99%
“…24 Some studies stated that tonsil and adenoid hypertrophy are major risk factors for OSA in children. 5,26 Hypertension status in subjects with OSA and non-OSA had no significant difference. This result was consistent with the study of Wiadnyana et al 17 that concluded the absence of correlation between hypertension and suspected OSA.…”
Section: Factors Associated With Osamentioning
confidence: 99%
“…Patients with OSA usually, but not always, present with suggestive signs and symptoms, such as loud breathing, snoring, poor feeding, hyperactivity, hypersomno- lence, behavorial problems, and poor quality of life 2 or failure to thrive. 6,21,23 However, OSA can be insidious and must be ruled out when any patient with craniosynostosis is evaluated. While there are a variety of traditional ways to assess OSA (Table 2), recently Bannink et al 3 developed the first OSA-specific QOL questionnaire (OSA-18) to address the impact of OSA in patients with syndromic craniosynostosis.…”
Section: Otolaryngology Assessmentmentioning
confidence: 99%